Factors influencing e-Health service in regional Bangladesh - Sayed, Moinul Islam; Mamun-ur-Rashid, Md. (International Journal of Health Sciences, 2021)
Objectives: This study probed the current status of e-health services use and associated factors that promote or hinder the people to get involved with e-health services. Methods: The quantitative data were collected using a structured interview schedule considering 381 randomly selected respondents covering rural and urban areas of Patuakhali, Jhalakathi, and Barishal district during February–April 2019. Only the adult (more than 18 years age) male, female, and transgender people living in the study area were included in the sample of the study. Descriptive statistics, Chi-square test, and binary logistic regression were used to analyze data. Results: Factors that significantly increased the likelihood of using e-health services included age (odds ratio [OR] = 1.05, 95% confidence interval [CI]:1.02–1.08), males (OR = 3.75, 95% CI: 1.70–8.26), knowledge in e-health (OR = 1.19, 95% CI: 1.02–1.38), and skill in using cell phone (OR = 1.11, 95% CI: 1.02–1.21). On the contrary, factor that negatively influenced the use of e-health services was residence in the rural area (OR = 0.209, 95% CI: 0.08–0.53). Although, this research is one of the few regional researches in e-health service use, the study has limited geographical coverage, failed to explore causality of factors, and did not address factors mediating the relationship of criterion and predictor variables. Conclusion: Regional e-health service providers in developing countries need to focus more on minimizing e-health service divide based on gender and place of residence. In addition, they should also emphasize digital literacy, particularly e-health knowledge and skill in device use. The findings of this study may provide an applied guideline to enhance the use of e-health services among regional communities in developing countries.